Extra Attention Toward Autistic Children: Islamic Psychology Perspective - Yopi Kusmiati; Achmad Syarifudin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Having an autistic child is a challenge for some parents because an autistic child should be treated specifically, based on condition and ability. The autistic child needs more extra attention than a non-autistic child because the attention from family can accelerate the development and ability of an autistic child, but not all parents can do the treatment because of various reasons. This study aimed to reveal the family's treatment which had an autistic child, especially parent or autistic's sister and brother. The study was done by using qualitative method with a phenomenological approach. The findings showed that there were three treatments of the family to treat an autistic child in daily life, they were extra attention, attention, and inattention. Extra attention was the informant included in the category who gave extra attention to a child. They were strongly caring about their child’s ability, food, and education. The attention category was an informant who did not fully give attention to their child, and not all time. The inattention category was an informant who rarely cares for their child, it related to the development of the child, education, and life.